Effect of Short-Term Exposure of Simulated Acid Rain on the Hemato-Immunological Parameters of the Purple Mangrove Crab Goniopsis pelii (Herklots, 1851) - Rasheed Olatunji Moruf (Covenant Journal of Physical and Life Sciences, 2021)
Acid rain is a broad term to describe the mixing of acid contaminant with rainwater. It has been detected in Nigeria's industrialized areas with effects on aquatic organisms. The effect of pH under rising stimulated acidic condition on the immune parameters of Purple Mangrove Crab (Goniopsis pelii) was investigated. The crabs were subjected to four experimental pH at 4.0, 5.0, 6.0 and 7.8 (control) in triplicates with 5 L of lagoon water. The short-term exposure period lasted for 14 days during which each plastic container was well aerated. Results showed that G. pelii exhibited marked reduction in hematological parameters between control and the exposed crab groups. There was a significant (P<0.05) reduction in haemoglobin from 2.63±1.52 g/dl in the control crabs to 0.95±0.01 g/dl in the pH 4.0 treatment. Significantly, higher alkaline phosphatase (70.92±3.24-75.44±4.01 μI-1) and albumen (3.21±0.06-6.44±0.09 gl-1) values were obtained in the treatments, increased with decrease in pH. The highest superoxide dismutase (260.93±6.11 min/mg pro) and catalase activities (2.447±1.25 min/mg pro) were recorded in the crabs exposed to pH 4.0. The malondialdehyde concentrations showed an increase from 10.41±1.91 nmol/ml to 10.77±2.02 nmol/ml, with decreasing pH and were significantly different from the 8.98±2.05 nmol/ml mean value of the control group. This finding suggests that decreasing pH is more detrimental to G. pelii survival under acidic condition. Hence, this pH-dependent phenomenon should be taken into consideration for optimal conservation of G. pelii.